IS THE PHONEME USAGE-BASED? – SOME ISSUES - Nathan, Geoffrey S. (International Journal of English Studies, 2009)
After a brief review of the history of the phoneme, from its origins in the nineteenth century to Optimality Theory, including some Cognitive Linguists’ views of the concept. I argue that current ‘usage-based’ theorists views of the phoneme may not be able to explain some facts about how naïve speakers process language, both consciously and subconsciously. These facts include the invention of and worldwide preference for alphabetic writing systems, and language processing evidence provided by Spoonerisms, historical sound changes affecting all (or most) lexical items in a language and each other, and the fact that allophonic processes normally do not show lexical conditioning. I further suggest that storing speech in terms of a small number of production/perception units such as phonemes could be due to the fact that phonemes seem to optimize both efficiency and informativeness in much the same way as other basic-level categories.